Possibilities of pharmacologic correction of cognitive disorders in conditions of experimental equivalent of multiple sclerosis - Nefyodov A.A.; Mamchur V.Io. (Medičnì Perspektivi)
A comparative analysis of the impact of citicoline, ±-lipoic acid, nicergoline, donepezil and colloidal solution of nano-silver (CSNS) on the processes of learning and consolidation of memorable track in the test of the conditional reaction of passive avoidance (CRPA) in conditions of experimental allergic encephalomyelitis (EAE) was conducted. Testing of passive defensive skill was performed on days 12 and 20 after the induction of EAE. To assess the impact of drugs on the inputted information processes the investigated substances were administered intragastrically (CSNS - intraperitoneally) once daily in the definite dose from the second to the day 10 after the induction of EAE (latent phase of the disease), and assessing processes of conditional skill preserving, further administration of drugs by the day 20 of the experiment (average duration of EAE) was used. A positive effect of citicoline, ±-lipoic acid, nicergoline and donepezil on the input information processes and the ability to prevent accelerated extinction of acquired contingent skill in the conditions of experimental pathology was established. Drugs statistically significantly increased duration of the latent period of CRPA in comparison with a group of active control by 49%, 43%, 39% and 34%, respectively. Here with preparations were characterized by a high coefficient of antiamnesic activity, by the end of the experiment it was recorded at the level of 95% (citicoline), 81% (±-lipoic acid), 76% (nicergoline) and 53% (donepezil). It is shown that the ability to prevent development of cognitive impairment in conditions of experimental equivalent of multiple sclerosis decreases in the number of citicoline (500 mg/kg) > ±-lipoic acid (50 mg/kg) H nicergoline (10 mg/kg) > donepezil (10 mg/kg).